Urgensi Kriminalisasi Perbuatan Kecurangan (Fraud) dalam Pelaksanaan Program Jaminan Kesehatan di Indonesia - Solehuddin Solehuddin (Universitas Jember, 2023)
In this study, the author discusses one of the problems regarding the Urgency of Criminalization of Fraud in the Implementation of the Health Insurance Program in Indonesia. The purpose of this study is to determine the urgency of criminalization of fraud in the implementation of health insurance programs in Indonesia and to determine the ideal concept of criminalization of fraud in the implementation of health insurance programs in Indonesia. The research method uses normative legal research, which is a process for finding legal rules, legal principles, and legal doctrines in order to answer the legal issues faced by the approach in this study using a research approach carried out a statutory approach (statute approach) and a conceptual approach (conceptual approach). The results of this study are Handling Fraud in the Implementation of the Health Insurance Program aims to provide a reference for Participants, BPJS Health, Health Facilities or health care providers, drug and medical device providers, and other stakeholders in organizing efforts to prevent and handle fraud in a systematic, structured and comprehensive manner so that the implementation of the Health Insurance program can run effectively and efficiently. So far, the prevention and handling of fraud is only the imposition of administrative sanctions against fraud in the implementation of the health insurance program, so it is very important to criminalize fraud in the implementation of the health insurance program in Indonesia. Keywords: Fraud, Health Insurance Program, Prevention